Comparison of body mass index criteria for the assessment of nutritional status in scholars - Leite, Neiva; Milano, Gerusa Eisfeld; Lopes, Wendell Arthur; Tanaka, Juliana; Dressler, Vanessa Freitas; Radominski, Rosana Bento (Journal of Physical Education (Maringá), 2008)
Purpose: To evaluate the prevalence of different nutritional status using school in the central region of Curitiba-Pr, comparing the agreement between the Brazilian, North-American and international cutoff points. Methods: Epidemiological study, with 1998 adolescents, 10-16 years of age. Height and body weight were measured. The nutritional status was classified by the Brazilian, North-American and international BMI cutoff points. Kappa index was calculated for agreement. Results: Brazilian reference and North-American resulted in a greater agreement in girls (k=0,96) and boys (k=0,88), similar were found in the comparison between North-American reference and international, in girls (k=0,95) and boys (k=0,93). There was strong agreement, in girls (k=0.96) and boys (k=0.90), between the Brazilian and international reference. The diagnosis of obesity didn’t differ among the three criteria, both genders. These results reinforce that it is possible to compare the prevalence of obesity even in studies that have applied different criteria.